SOSIALISASI PERAN WIRAUSAHA MELALUI EDUKASI KEWIRAUSAHAAN PADA IBU-IBU ANGGOTA PEMBINAAN KESEJAHTERAAN KELUARGA (PKK) DALAM MENINGKATKAN PEREKONOMIAN KELUARGA DI DESA - Anwar, Nursyam; Sumarsih, Sumarsih (Unit Publikasi dan Jurnal Sekolah Tinggi Ilmu Ekonomi Tri Dharma Nusantara Makassar, 2023)
: Community Service is one of the activities carried out by academics to provide knowledge to the community which can be implemented both socially and economically. The Lapeo Village PKK group has some potential to produce local products that can have sales value. Through this community service training, the aim is to provide entrepreneurial outreach to PKK administrators and members in order to provide knowledge that can be applied to businesses run by PKK women in Lapeo Village. The Lapeo Village PKK group faces several problems, especially regarding knowledge of starting a business properly and correctly. The first problem faced is a lack of knowledge about entrepreneurship itself. The second problem is the lack of knowledge about the stages and processes of entrepreneurship which must be understood by every mother who is interested in doing business. The third problem is a lack of knowledge about the factors of success and failure in entrepreneurship that must be anticipated and understood by every entrepreneur and mother who is interested in doing business. The solutions offered in community service activities are 1) Increased understanding of entrepreneurship, especially for women who are administrators and PKK members of Lapeo Village, to maximize and increase the spirit of entrepreneurship in Lapeo Village. The proposed activity plan is 1) Preparation stage, 2) Socialization of the Role of Entrepreneurs through Entrepreneurship Education for Mothers, Members of Family Welfare Development (Pkk) in Improving the Family Economy in Lapeo Village, District. Campalagia